Analisis Faktor-faktor yang Memengaruhi Konsumen dalam Keputusan Pembelian pada Coffee Shop di Kota Denpasar - KADEK ENDRA ABHYAMANTA; MADE ANTARA; I G.A.A LIES ANGGRENI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
Analysis of The Factors Affecting Consumer Purchasing Decision at Coffee Shops in Denpasar City The intensifying competition between coffee shop businesses in Denpasar City has demanded entrepreneurs to understand the behavior and factors that influence consumer purchasing decisions. This study aims to identify the characteristics of consumers; analyze consumer responses; and analyze the influence of product, price, place, promotion, service, personal factors, and socio-culture on consumer purchasing decisions at coffee shops in Denpasar City. The results showed that the characteristics of coffee shop consumers in Denpasar City are dominated by females; young people between 19-24 year old; students; people with monthly income under Rp. 500.000,-; visiting coffee shops once a month; and live in South Denpasar. Consumer responses show neutral responses to personal factors, but agreeing to products, prices, places, promotions, services, and socio-cultural factors. Product, price, promotion and socio-cultural factors have a positive and significant effect; places have a negative but significant effect; service and personal factors have a positive but not significant effect on consumer purchasing decisions at coffee shops in Denpasar City. Coffee shop entrepreneurs in Denpasar City should improve product quality, price, place, promotion, and socio culture, in order to improve consumer purchasing decisions.